STRES KERJA DAN KESIAPAN UNTUK BERUBAH: PERANAN STRATEGI KOPING SEBAGAI MODERATOR - Fridayanti Fridayanti; Qanita Zahra; Farid Soleh Nurdin (Jurnal Psikologi, 2023)
This study aims to determine the effect of work stress on readiness to change with coping strategies as a moderating variable. We used a cross-sectional survey design for 124 archivists, 58 men, and 66 women. For data analysis, we conducted regression and moderation analysis. We collected data using a questionnaire consisting of three measuring tools: Job Stress Scale (JSS), Readiness for Change Scale, and Brief-Cope. The results showed that work stress significantly affected readiness to change, with a coefficient of determination of 86.4%. Adaptive coping strategies act as moderators and strengthen the effect of work stress on readiness to change with an increase in the coefficient of determination to 87.9% and a beta coefficient of .020. However, maladaptive coping strategies cannot act as a moderator in the effect of job stress on readiness to change.